The Flexural Strength and the Effect of the Autoclave Sterilization of Polypropylene/Natural Rubber Blended Materials - Paphavarin Rangsantham; Thitaporn Nonthiphalang; Panjaporn Wongwitthayakool; Chakrit Sirisinha; Nantawan Krajangta; Panupat Phumpatrakom (Dentistry Journal)
Background: Rubber dam clamps are used extensively in dentistry, especially during root canal treatment. However, existing rubber dam clamps have several drawbacks, including discomfort and potential damage to vital tissue in the oral cavity. To address these existing issues, a new rubber dam clamp should be developed. The aim of this study was to identify the optimum ratios of polypropylene and natural rubber (PP/NR) for a customized rubber dam clamp in dentistry. This study was focused on the flexural strength of PP/NR in various ratios. Moreover, the impact of autoclave sterilization was also considered. Methods: Six proportions of PP/NR blends (100/0, 90/10, 80/20, 70/30, 60/40 and 50/50) were prepared and assessed for flexural strength using a three-point bending test. After this test, the PP/NR blends with 100/0, 90/10 and 80/20 ratios were selected and underwent autoclave sterilization for 1, 5 and 10 cycles. Eventually, the flexural strength testing was repeated and investigated. An analysis of variance and Tukey’s test were used to evaluate the flexural strength of various PP/NR blends before autoclave sterilization at p < 0.05. An analysis of variance and Dunnett’s T3 test were used to evaluate the flexural strength of selected PP/NR blends before and after autoclave sterilization at p < 0.05. Results: The results revealed that the flexural strength of PP/NR blended materials showed a statistically significant difference in every group of this study. The autoclave sterilization test revealed that the flexural strength of the PP/NR 90/10 and 80/20 ratios was significantly increased after sterilization for 1, 5 and 10 cycles. In addition, the PP/NR 90/10 ratio was also comparable to the 100/0 ratio. The lower NR content in PP/NR blends resulted in significantly higher flexural strength, and autoclave sterilization had an effect on this property. Conclusions: This study suggested that the PP/NR blend with a 90/10 ratio might be considered as an alternative material for developing rubber dam clamps.